(untitled) (Medical Forum Monthly, 2024)
Objectives: To evoke law enforcement agencies for batter legislative measures against increasing trend of battering of wives in Pakistan. Study Design: Cross Sectional / Analytic Study Place and Duration of Study: This Study was conducted at the Emergencies & OPDs Departments Islam Teaching Hospital, Sialkot, District Headquarter Hospital, Gujranwala, Rehmat Memorial Hospital, Lahore, Ameer ud din Memorial Hospital, Peshawar and Shahina Jamil Hospital, Abbottabad from 1st January 2012 to 31st May 2013. Materials and Methods: Total 169 cases of battered wives were reported but 100 cases of battered wives out of 169 who consented were selected in the study. A proforma was specially designed to include different influential criteria like age, socio economic group, combined or joined family system, education, mental or physical health and addiction. Results: Out of 100 cases who were selected the maximum incidence was among the young age group ranging between 21 to 30 years 56% in low socio economic group, 83% in suppose of addicted partners, 63% in illiterate couples, 67% in joined family system. Poor physical and mental health of wife is another precipitation factor amounting to 83%. Conclusion: The tendency of battered wife is a global problem. It is increasing day by day in developed / under developed countries and nations. This trend is even going to be increased in Muslim countries where battering to the wife is prohibited (Haraam). Increasing tendency in Pakistan is mainly due to illiteracy addiction, financial stresses and low standards of living which in turn are the basis of poor physical and psychological health.